DAKWAH DAN PROSES PENYEBARAN ISLAM DI INDONESIA - Farid, Ahmad; Fitriyani, Kurnia Nur; -, Murodi; Yakin, Syamsul (LP2M IAIN Syekh Nurjati Cirebon, 2024)
The development of Islamic propagation (dakwah) and the dissemination of Islam in Indonesia have been simultaneous and complex. Dakwah, which linguistically means a religion that brings salvation, has been widely accepted by the majority of Indonesian society. This success cannot be separated from the roles of past propagators who utilized various dakwah methods, namely dakwah bil lisan (oral preaching), bil kitabah (written preaching), and bil hal (practical preaching). This paper aims to analyze the process of dakwah and the spread of Islam in Indonesia using the theoretical framework of structural functionalism. The research employs a descriptive qualitative method with a library research approach, focusing on studies of dakwah and the spread of Islam. The findings indicate that Islam entered Indonesia through trade, marriage, education, sufism, arts, and politics. The primary propagators of Islam in early Indonesia were the Walisongo, who arrived periodically. The arrival of Islam elicited various responses from the mad'u (recipients of dakwah), which eventually led to widespread acceptance. The dynamics of accepting Islamic teachings were influenced by the social class context of the past, specifically the abangan, santri, and priyayi classes.